Ultraviolet laser induced periodic surface structures positively influence osteogenic activity on titanium alloys - Schweitzer, Luiz; Schoon, Janosch; Bläß, Niklas; Huesker, Katrin; Neufend, Janine V.; Siemens, Nikolai; Bekeschus, Sander; Schlüter, Rabea; Schneider, Peter; Uhlmann, Eckart; Wassilew, Georgi; Schulze, Frank (Frontiers in Bioengineering and Biotechnology, 2024)
Background/Objective: Endoprostheses might fail due to complications such as implant loosening or periprosthetic infections. The surface topography of implant materials is known to influence osseointegration and attachment of pathogenic bacteria. Laser-Induced Periodic Surface Structures (LIPSS) can improve the surface topography of orthopedic implant materials. In this preclinical in vitro study, laser pulses with a wavelength in the ultraviolet (UV) spectrum were applied for the generation of LIPSS to positively influence formation of extracellular matrix by primary human Osteoblasts (hOBs) and to reduce microbial biofilm formation in vitro. Methods: Laser machining was employed for generating UV-LIPSS on sample disks made of Ti6Al4V and Ti6Al7Nb alloys. Sample disks with polished surfaces were used as controls. Scanning electron microscopy was used for visualization of surface topography and adherent cells. Metal ion release and cellular metal levels were investigated by inductively coupled plasma mass spectrometry. Cell culture of hOBs on sample disks with and without UV-LIPSS surface treatments was performed. Cells were investigated for their viability, proliferation, osteogenic function and cytokine release. Biofilm formation was facilitated by seeding Staphylococcus aureus on sample disks and quantified by wheat germ agglutinin (WGA) staining.Results: UV-LIPSS modification results in topographies with a periodicity of 223 nm    278 nm.The release of metal ions was found increased for UV-LIPSS on Ti6Al4V and decreased for UV-LIPSS on Ti6Al7Nb, while cellular metal levels remain unaffected. Cellular adherence was decreased for hOBs on UV-LIPSS Ti6Al4V when compared to controls while proliferation rate was unaffected. Metabolic activity was lower on UV-LIPSS Ti6Al7Nb when compared to the control. Alkaline phosphatase activity was upregulated for hOBs grown on UV-LIPSS on both alloys. Less proinflammatory cytokines were released for cells grown on UV-LIPSS Ti6Al7Nb when compared to polished surfaces. WGA signals were significantly lower on UV-LIPSS Ti6Al7Nb indicating reduced formation of a Staphylococcus aureus biofilm. Conclusion: Our results suggest that UV-LIPSS texturing of Ti6Al7Nb positively influence bone forming function and cytokine secretion profile of hOBs in vitro. In addition, our results indicate diminished biofilm formation on UV-LIPSS treated Ti6Al7Nb surfaces. These effects might prove beneficial in the context of long-term arthroplasty outcomes.